A One- or Two-Stage Revision of Fungal Prosthetic Joint Infection: A Review of Current Knowledge, Pitfalls and Recommendations - Hazem Alkhawashki; Joseph Benevenia; Lorenzo Drago; Yazan Kadkoy (Antibiotics, 2025)
Fungal prosthetic joint infection (fPJI) is one of the orthopaedic pathologies where there is no clear evidence, guidelines or algorithm to guide the surgeon in its management. This is in addition to the difficulty with which these infections are diagnosed, isolated and treated. Fungi form notorious biofilms that are difficult to eradicate once formed and that display resistance to antimicrobial agents. These biofilms have been shown to act synergistically with biofilms of bacteria, further adding to medical treatment resistance. We have reviewed the literature for reports that describe the results of different methods in surgically treating fPJI. We found that surgical management with two stages remains the gold standard for treatment of fPJI, as is the case for bacterial PJI (bPJI). We have investigated medical treatment, debridement with implant retention (DAIR) and staged revisions and whether a reasonable recommendation can be made based on the best knowledge and practice available. From the data on bPJI, there exists a role for conservative management of acute PJI with debridement, antibiotics and implant retention (DAIR). While fPJI and bPJI both represent infections, the differences in our ability to detect these infections clinically, culture the pathogens and treat them with proper antimicrobial agents, along with the difference in the reported results of the surgical treatment, make us believe that these two types of infections should not be treated in the same manner. With all this in mind, we reviewed several reports in the literature on fPJI to determine the efficacy of current treatment modalities, including DAIR, which followed current guidelines for PJI. Data show an overall treatment success rate of 64.4% [range 17.4–100%]. Subgroup analysis revealed a success rate of 11.6% [range 0–28.7%] in patients treated with DAIR. There is no doubt that DAIR should not be encouraged as it consistently has a bad record. Although there are not enough studies or numbers of patients to show an evidence-based preference over one- or two-staged revisions, the two-stage revision of fPJI consistently shows better results and should be considered as the gold standard of management in cases of revision fPJI. This should also be coupled with proper expertise, follow-ups and recommended lengths of medical treatment, which should not be less than six months. From the review of these data, we have developed reasonable recommendations for the management of fPJI. These recommendations center on staged surgical debridement along with medical management. Medical treatment should be for at least 6 months under the guidance of an infectious disease team and based on intraoperative cultures. In the case of local antimicrobial treatment reported in the literature, many patients with fPJI were found to have a polymicrobial infection. As a result, it is our recommendation that antifungals as well as antibacterials should be incorporated into the cement spacer mix of these cases. Fungal PJI remains an exceedingly difficult pathology to treat and should be managed by experienced surgeons in a well-equipped institution.